(untitled) (Baghdad Science Journal, 2011)
The study aims at showing the effect of basil oil on the sensory properties of the laboratory biscuits. the results show the sensory valuation before and after the storage. the (A4) equation exceeds 15% of T exchange (3 , 4 , 5 g. basil 19 , 55 g . fats )in most of the studied sensuous qualities. Then, the (A5) equation of 20% exchange percentage (4.60g. basil oil + 18.40g. fats). Then, the (A3) equation of 10% exchange percentage (2.30g. basil oil + 20.70g. fats). Then the (A2) equation of 5% exchange percentage (1.5g. basil oil + 21.85g. fats). Finally, the control equation (A1) received the lower value of sensuous evaluation and general acceptance. Abstract differences also appeared at denotation level 0.05 between the (A2) , (A3), (A4), (A5) and (A1). Some Abstract differences also appeared between each equation and the others in special quality, or the absence of another. the values of L.S.D. is also discovered the flavor quality get the highest value which reached (0.610) while the softness quality get the lower value which reached (0.323) before the storage . While after storage the general acceptance gets the higher value of 0.544 While the color quality gets the lower value of 0.314. Considering the effects of Oil in lengthening the storage duration, some micoropic fest procedures were performed to identify the type of the microscopic creature that grows during the storage period and continued for 5 months. The tests results show the growth of Bacteria in the treatment which is stapyllococcusspp. Appositive Bacteria for Gram paint at 37c degree during 5 months of storage. A growth of Bacteria also appeared during the last week of the fifth months of the treatment (A2) and the oil rate is 5% , since the number reached 8× 103 colony mm. millieme .